Enhancing Learning Experience: A Study of Students' Needs for Pocket Books in the Digital Era - Syafriyeti, Rahmi; Eriyanti, Ribut Wahyu; Rofiq, Ainur; Huda, Atok Miftahul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Background: the religious values play a crucial role in shaping the character and morals of students, and understanding the views of lecturers regarding this matter can provide profound insights to enhance higher education. Aim: Analyzing lecturers' perceptions regarding Islamic values entails focusing on their awareness levels, integration of religious values into the curriculum, the role of lecturers in shaping character, institutional support, and the influence of understanding Islamic values on students' morality. Method: This research employed a survey method involving 60 lecturers as respondents. The survey comprised structured questions covering the importance level of Islamic values, their integration into the curriculum, the role of lecturers, institutional support, and perspectives regarding the influence of understanding Islamic values on students. Results and Dıscussion: The survey results indicate that a majority of the lecturers are aware of the significance of Islamic values (91.6%), and most of them (80%) feel that these values are sufficiently integrated into the curriculum. There is substantial support for the role of lecturers in shaping Islamic character (88.4%), and a significant portion of the lecturers (78.3%) feel they receive adequate institutional support. Overall, the results reflect a positive outlook from the lecturers regarding Islamic values. Conclusion This research highlights the importance of supporting lecturers in strengthening their role as character-forming agents and emphasizes the necessity of integrating religious values into higher education curricula. The implications of these findings can assist in designing policies and more holistic educational strategies, fostering an educational environment focused on the development of student character and morality.